ANALISIS PROGRAM RESTRUKTURISASI KREDIT DALAM MENINGKATKAN KINERJA BANK BRI SUMENEP (STUDI KASUS SELAMA MASA PANDEMI COVID 19) - Umyana, Siti (International Journal of Science, Engineering, and Information Technology, 2025)
A credit that is said to be bad must have a rescue effort, if leftunchecked it will cause losses to the bank. Rescue can be done by restructuring (rearrangement). With restructuring in accordance with the condition of debtors who are potentially unable to pay, the liquidity of a bank can be maintained. One of the banks that issued a policy for implementing credit restructuring, namely BankBRI, Bank BRI Sumenep Branch is the branch with the most BRI Bank Units on Madura Island which also implemented a credit restructuring program. The purposeof this study is to determine the credit restructuring program and its implications for improving the performance of Bank BRI Sumenep Branch. This study uses a qualitative approach and the type of field research, while the data analysis uses the stages of data collection, data reduction, data presentation, and verification/drawingconclusions.The results of this research are first, the BRI Sumenep branch of the bank carried out a credit restructuring program in 3 ways, namely extending the term, reducing interest rates, and grace periodi. and the needs of debtorsin Sumenep Regency. The recipient of the credit restructuring must meet 3 criteria, namely (1) there is good faith from the debtor/cooperative, (2) business prospects are still good, and (3) the business is still running, but during Covid-19 the criteriafor credit restructuring recipients were relaxed to become only 1, namely 'the business is still running'. Second, The credit restructuring program carried out by Bank BRI Sumenep Branch is considered successful in reducing the level of non-performing loans, namely by May 2022 the data on the number of restructured accounts has reached 17 accounts from 21 accounts in December 2021 and in nominal terms in May 2022 only Rp. 10,142,857,142 from Rp.15,371,461,327 in December 2021. So that the performance of Bank BRI Sumenep Branch is getting better after the credit restructuring program